2002
DOI: 10.1046/j.1525-1438.2002.01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of metallothionein in benign and malignant epithelial ovarian tumors

Abstract: Metallothioneins (MTs) are a group of low-molecular-weight proteins that are overexpressed in a variety of human neoplasms and are related to differentiation and prognosis in some tumor types. This study investigated immunohistochemically detectable metallothionein expression in benign and malignant ovarian surface epithelial tumors of serous, mucinous, and endometrioid types. MT expression was observed in 56% of carcinomas (n = 139) and in 2% of benign neoplasms (n = 81). Of the malignant tumors, MT expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…The studied group was uniform: 95% of the patients were in FIGO stage III, 86% of the studied cases involved serous carcinoma, 98% of the patients were treated with cisplatin-based schemes and 2% or one patient with a carboplatin-based scheme. We confirm that the studied proteins are expressed in ovarian carcinomas [2,17]. We have found that intensity of MT expression is higher in sections from second-look procedures (after chemotherapy) and that there is no difference in expression intensity of GST-pi between sections from primary laparotomies and second-look procedures.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The studied group was uniform: 95% of the patients were in FIGO stage III, 86% of the studied cases involved serous carcinoma, 98% of the patients were treated with cisplatin-based schemes and 2% or one patient with a carboplatin-based scheme. We confirm that the studied proteins are expressed in ovarian carcinomas [2,17]. We have found that intensity of MT expression is higher in sections from second-look procedures (after chemotherapy) and that there is no difference in expression intensity of GST-pi between sections from primary laparotomies and second-look procedures.…”
Section: Discussionsupporting
confidence: 84%
“…zinc and copper), alleviation of toxic effects of cadmium and mercury or protection of cells from oxidative stress [6,11]. Numerous reports document MT presence in cells of various tumors, including ovarian cancer [3,7,17,28].…”
Section: Introductionmentioning
confidence: 99%
“…A total of four studies were identified [57][60]. All studies except for Tan et al reported a significant increase [59].…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between MT expression and cisplatin sensitivity has been clearly demonstrated in cultured cells [137] , and there is evidence in support of this association from clinical studies. MT expression is elevated in oesophageal, ovarian, ductal mammary tumours and adenocarcinoma of the large intestine [73,[138][139][140] ; and moreover, correlations between expression and the resistant phenotype have been observed in both oesophageal [73] and urothelial [128] cancers. The ovarian cancer study indicates that increased expression of MT is associated with a poor prognosis.…”
Section: Detoxification Of Platinum Complexesmentioning
confidence: 99%